Systematic Investigation of Heart Sound Propagation using Continuous Wave Radar - Oesten, Marie; Abel, Luca; Albrecht, Nils C.; Richer, Robert; Langer, Dominik; Grießhammer, Stefan; Ghanem, Khalida; Steigleder, Tobias; Ostgathe, Christoph; Koelpin, Alexander; Eskofier, Björn (IEEE Journal of Biomedical and Health Informatics, 2025)
Monitoring the propagation of mechanical cardiac signals throughout the body is crucial for assessing cardiovascular health. A common drawback of current gold standard methods for vital sign monitoring is the necessity for continuous skin contact. Radar-based sensing offers a promising alternative by enabling contactless measurement of cardiac activity, including heart sound signals. As previous research has primarily focused on deriving signals from proximal body regions, insights into heart sound propagation to peripheral areas are lacking. To address this, we systematically investigated whether radar-based heart sound detection and propagation measurement is feasible across the whole body. We recorded heart sounds in N=22 participants sequentially at eleven locations using a custom-built continuous-wave radar system and phonocardiogram as heart sound gold standard. Additionally, an electrocardiogram was acquired as reference for overall heart activity. After synchronization and preprocessing, we manually segmented the heart sounds and extracted temporal characteristics from ensemble-averaged signals. Our findings show that heart sounds can be detected across the entire body with the radar-based as well as the gold standard system. Furthermore, the heart sounds’ temporal characteristics vary between measurement locations. As the distance to the heart increases, we observed significantly increased propagation time intervals. This finding is consistent across both systems, exhibiting a strong agreement for the first heart sound (r = 0.73, p < 0.001) and a moderate agreement for the second heart sound (r = 0.56, p < 0.001). In conclusion, our work is the first to demonstrate that radar-based systems are feasible for contactless evaluation of heart sound propagation, offering new possibilities for research and health monitoring.
CRIS-Team Scopus Importer:2025-01-31
Keywords: biomedical radar; full-body; hemodynamic evaluation; phonocardiogram